2013
DOI: 10.1590/s0102-695x2013000100019
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antinociceptive activities of Phyllanthus niruri spray-dried standardized extract

Abstract: Phyllanthus niruri L., Euphorbiaceae, spray-dried standardized extract was studied for its anti-infl ammatory and antinociceptive activities in adult albino rats and mice. The anti-infl ammatory effect of spray-dried standardized extract was observed in carrageenan-induced paw edema and thioglycolate-induced leukocyte migration, while antinociceptive effects were observed using Randall & Selitto, tail fl ick, and hot plate tests. This study showed that intraperitoneal spray-dried standardized extract at 100, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The anti-inflammatory activity of meniran is evidenced by a decrease in oedema volume in the treatment group by 58% which is greater than the positive control (indomethacin), which only has an oedema reduction effect of 43% (Sumarny et al, 2013). Anti-inflammatory is produced because meniran is rich in phenolic compounds, especially flavonoids, namely quercetin (Porto et al, 2013). Due to the content of phytoconstituents in meniran, such as flavonoids, steroids, triterpenoids, saponins, and tannins, there is another pharmacological effect, namely as an antiulcer as evidenced in the study of Mostofa et al, (2017), where methanol extract of meniran has a potential effect as an antiulcer at a dose of 400 mg /kg by comparison with the standard drug, namely omeprazole.…”
Section: Phyllanthus Niruri Lmentioning
confidence: 99%
“…The anti-inflammatory activity of meniran is evidenced by a decrease in oedema volume in the treatment group by 58% which is greater than the positive control (indomethacin), which only has an oedema reduction effect of 43% (Sumarny et al, 2013). Anti-inflammatory is produced because meniran is rich in phenolic compounds, especially flavonoids, namely quercetin (Porto et al, 2013). Due to the content of phytoconstituents in meniran, such as flavonoids, steroids, triterpenoids, saponins, and tannins, there is another pharmacological effect, namely as an antiulcer as evidenced in the study of Mostofa et al, (2017), where methanol extract of meniran has a potential effect as an antiulcer at a dose of 400 mg /kg by comparison with the standard drug, namely omeprazole.…”
Section: Phyllanthus Niruri Lmentioning
confidence: 99%
“…It is identified in Amazon rainforest and other tropical areas, including South East Asia, Southern India, and China. P. niruri L. has been extensively reported in traditional and folk medication systems such as Ayurveda and Siddha to treat various diseases including diabetes mellitus, jaundice, asthma, joint pain, immunomodulator, loss of appetite, constipation, injuries, as antimicrobial, conjunctivitis, gonorrheal diseases of males and females, inflammatory diseases, skin itching, kidney stones or failures, and urogenital disease [4][5][6][7][8][9][10][11][12][13][14][15][16]. Curative properties of P. niruri are due to the presence of polyphenols, include classes of chromones, coumarins, lignans, stilbenes, xanthones, and flavonoid [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of this herb have been proven to have therapeutic effects in many preclinical studies. Phyllanthus niruri has been reported to be an effective anti-inflammatory [ 12 ], analgesic [ 13 ], gastroprotective [ 14 ], anti-diabetic [ 15 ], hepatoproctive [ 16 – 18 ], anti-malarial [ 19 , 14 ] and antispasmodic [ 20 ]. In Bangladesh, P. niruri grows all over the country.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, P. niruri grows all over the country. According to a previous study, the aerial part of this plant has been reported for its anti-inflammatory activity [ 12 ]. Besides, it has been stated that the leaves of P. niruri contain profound amount of flavonoids and polyphenolics [ 21 ] which possess significant activity against inflammation and ulcer [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%